Personal, Socio-economic Characteristics of Buffalo Owners of Peri-urban areas of Surat, Gujarat (Indian Journal of Animal Production and Management, 2024)
A field survey was conducted in Peri-urban areas of Surat city of Gujarat to ascertain the personal,  socio-economic characteristics of buffalo owners and data were collected from randomly selected 50  buffalo farm owners through personal interview with the help of pre-tested structured schedule. The  study revealed that majority of the buffalo owners were belonged middle to old age group, literate,  nuclear type of family having more number of children making big size family. All of the respondents  were from other backward category having medium level of extension contacts and mass media  exposure with membership in one organization. Majority of the respondents were falling under  marginal to small categories farmers with small herd size and they possessed agriculture and  livestock as their livelihood.
Keywords: Buffalo owners; characteristics; personal; socio-economic; peri-urban areas